Separation of solids and disinfection for agronomical use of the effluent from a UASB reactor - Sundefeld Jr., G.C.; Piveli, R.P.; Cutolo, S.A.; Ferreira Filho, S.S.; Santos, J.G.
The present work addresses the preparation of the effluent from a full-scale upflow anaerobic sludge blanket (UASB)reactor for drip irrigation of orange crops. The pilot plant included a lamella plate clarifier followed by a geo-textile blanket filter and a UV disinfection reactor. The clarifier operated with a surface load of 115 m3 m-2 d-1, whereas the filter operated with 10 m3 m-2 d-1. The UV reactor was an open-channel type and the effective dose was approximately 2.8 W h m-3. The effluent of the UASB reactor received 0.5 mg L -1 cationic polyelectrolyte before entering the high-rate clarifier. Suspended solids' concentrations and Escherichia coli and helminth egg's densities were monitored throughout the treatment system for 12 months. Results showed that the total suspended solids concentration in the filter effluent was lower than 7 mg L-1 and helminth density was below 1.0 egg L -1. The UV disinfection demonstrated the ability to produce a final effluent with E. coli density lower than 103 MPN/100 mL (MPN: most probable number)during the entire process. Thus, the World Health Organization standards for unrestricted crop use were met. Agronomic interest parameters were controlled and it was possible to identify the important contribution of treated sewage in terms of the main nutrients.
Keywords: CATIONIC POLYELECTROLYTE; GEO-TEXTILE BLANKET FILTER; MOST PROBABLE NUMBER; TOTAL SUSPENDED SOLIDS; UASB REACTOR; ULTRAVIOLET DISINFECTIONS; UP-FLOW ANAEROBIC SLUDGE BLANKET REACTORS; WORLD HEALTH ORGANIZATION